Examining Influence of Forensic Accounting Skills and Education on Fraud Detection: Mediating Role of Job Satisfaction - Alsheikh, Warda (The Arab Journal of Administration, 2025)
In such a backdrop, drawing on both Job Demands–Resources (JD–R) model and Human Capital Theory, this study aims to investigate the impact of forensic accounting education and skills on fraud detection among accounting practitioners in Saudi Arabia, while also evaluating the role of job satisfaction as a mediating factor in these interactions. Data were collected from a probability-based simple random sample of private-sector accounting practitioners through a survey questionnaire. Partial Least Squares-Structural Equation Modelling (SmartPLS-4) was employed to test the hypotheses. The results show that both forensic accounting education and forensic accounting skills have positive and significant influence on fraud detection. Moreover, the study found job satisfaction as a mediator for both relationships. By combining JD–R and Human Capital Theory at the practitioner level, it improves the basic principles of fraud detection and helps with methods for building skills and getting people involved in emerging markets. Moreover, this study offers unique, context-specific data from Saudi Arabia that connects forensic education and skills to fraud detection, revealing job satisfaction as an innovative mediating factor. The study has implications for businesses, academics, and policymakers.